ASUPAN ZAT GIZI DAN STATUS GIZI PADA REMAJA PUTRI YANG SUDAH DAN BELUM MENSTRUASI - Dyan Fajar Christianti; Ali Khomsan (Jurnal Gizi dan Pangan, 2012)
The objective of this study was to analyze nutrient intake and nutritional status of menstruating and non-menstruating girls. This survey was conducted from April to September 2012 in elementary schools and junior high schools in Bogor. Total subjects consisted of 35 menstruating and 35 non-menstruating girls who were chosen through screening. The results showed that the percentage of menstruating girls in urban (28.0%) were more than in rural (25.1%). About 57.1% of subjects had menarche at 10 years old. The average of nutrient intake on menstruating and non-menstruating girls were under DRI (<90%). Overweight was more prevalent in menstruating subjects (14.3%) compared with non-menstruating subjects (2.9%). Similarly, the percent body fat measurement results showed that overweight and obese subjects were more prevalent in menstruating subjects (17.2%) compared with non-menstruating subjects (2.9%). Independent sample t-test showed significant differences in age, energy and calcium intake, BMI/age, and percent body fat between menstruating and non-menstruating subjects (p<0.05).